Procuring Microdata Files for the LIS Project Databank: Progress and Promise - Timothy M. Smeeding (Luxembourg Income Study (LIS), 2001)
The Luxembourg Income Study (LIS) project is one of the oldest and best known examples of crossnational social science infrastructure. Some 25 nations and 20 sponsors team together to provide internet accessible, privacy-protected, household income microdata to over 400 users in 30 nations. The project is financed by annual contributions by 16 nations National Science Foundations and/or National Statistical Offices. One of the most crucial pieces of the LIS structure is the source and type of data that it offers to its users. This paper describes these data, how they are obtained, harmonized, and made available. It presents a critical discussion of where the project is today and where and how international data collection efforts can improve upon both the quality of income data and its dissemination to qualified researchers.
Keywords: 330; Einkommensstatistik; Statistische Methode; Anpassung; Digitale Güter; OECD-Staaten